In-Silico Design of Functionally Graded Electrodes for Solid Oxide Fuel Cells. (10th July 2019) - Yan, Zilin; He, An; Hara, Shotaro; Shikazono, Naoki
Abstract : In this paper, microstructures of functionally graded (FG) electrodes for solid oxide fuel cells are modeled using sequential numerical simulations. Porosity gradient with linear and nonlinear profiles are considered for La0.6 Sr0.4 Co0.2 Fe0.8 O3-δ (LSCF) cathodes. First, the realistic three-dimensional (3D) LSCF particles are reconstructed using FIB-SEM tomography and collected as particle templates. These digital particles are packed using a multi-sphere discrete element method (DEM). Green LSCF cathodes are numerically formed by depositing layers of LSCF powders with graded volume fractions of pore formers in DEM simulations. Then, the FG-green cathodes by DEM are numerically sintered with a kinetic Monte Carlo (KMC) method. 3D microstructures by the KMC are passed to a lattice Boltzmann method (LBM) to calculate the cathode overpotential. The thermal stability of the cathodes are assessed by the KMC simulation. Finally, the effects of the porosity and porosity gradient on the overpotential and durability of FG-cathode are evaluated and discussed.